2021
DOI: 10.1002/ana.26135
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Light Chain in Patients with COVID‐19 and Bacterial Pneumonia

Abstract: We read with great interest the recent article by Sutter and colleagues reporting increased serum neurofilament light chain (NfL) levels in COVID-19 patients compared to non-COVID-19 intensive care unit (ICU) patients without infectious disease. 1 They postulated that infection with SARS-CoV-2 leads to neuronal injury in ICU-patients and that NfL might be used to identify patients at risk for neurological complications.We evaluated these findings in the broader context of infectious disorders by comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
5
20
0
Order By: Relevance
“…Our results confirm previously published findings that patients hospitalized with severe COVID-19 have elevated biomarkers of CNS injury in their blood. 6 , 21 - 25 This finding therefore supports the body of literature showing that COVID-19 neurologic sequelae in the acute phase are accompanied by damage to the CNS despite the fact that direct SARS-CoV-2 infection of the brain parenchyma remains a matter of debate. 26 In severely ill patients, the possible causes of CNS injury include hypoxemia, vasculopathy, coagulopathy, or systemic inflammation leading to blood-brain barrier disruption.…”
Section: Discussionsupporting
confidence: 85%
“…Our results confirm previously published findings that patients hospitalized with severe COVID-19 have elevated biomarkers of CNS injury in their blood. 6 , 21 - 25 This finding therefore supports the body of literature showing that COVID-19 neurologic sequelae in the acute phase are accompanied by damage to the CNS despite the fact that direct SARS-CoV-2 infection of the brain parenchyma remains a matter of debate. 26 In severely ill patients, the possible causes of CNS injury include hypoxemia, vasculopathy, coagulopathy, or systemic inflammation leading to blood-brain barrier disruption.…”
Section: Discussionsupporting
confidence: 85%
“…An increase in serum or CSF NfL has been previously associated with increased ICU mortality due to sepsis‐associated encephalopathy 8 . This study expands these data to COVID‐19 ICU admissions: First, we validated reports linking high serum/plasma NfL levels to COVID‐19 severity 9–13,22,23 . Our longitudinal measurements demonstrated that rise in NfL generally occurs during hospitalizations of critically ill patients and trails other transient laboratory abnormalities such as decreased ALC and increased LDH by 5–20 days.…”
Section: Discussionsupporting
confidence: 65%
“…8 This study expands these data to COVID-19 ICU admissions: First, we validated reports linking high serum/plasma NfL levels to COVID-19 severity. [9][10][11][12][13]22,23 Our longitudinal measurements demonstrated that rise in NfL generally occurs during hospitalizations of critically ill patients and trails other transient laboratory abnormalities such as decreased ALC and increased LDH by 5-20 days. The degree of LDH increase is a strong determinant of the subsequent magnitude of NfL rise, suggesting that COVID-19-associated CNS injury is secondary to damage of other critical organs, such as liver, kidneys, and lungs.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…By not making the distinction of biochemically normal versus biochemically abnormal dystrophin, the authors may inadvertently heighten the expectations of patients, families, physicians, and regulatory agencies regarding anticipated clinical benefit from very low levels of semifunctional dystrophin. 1…”
mentioning
confidence: 99%